THE EFFORTS OF FEMALE CHARACTERS FIGHT AGAINST GENDER DISCRIMINATION REVEALED IN HIDDEN FIGURES MOVIE - ANDINTYA FARADILLA (Dinamika Bahasa dan Budaya, 2020)
ABSTRAK This study reveals kinds of gender discrimination experienced by female characters and their efforts against gender discrimination in Hidden Figures movie by Theodore Melfi. The purpose of this study is to find kinds of gender discrimination happen towards female characters and their effort to against gender discrimination based on power feminism which applied in this problem to show that they are strong female character. In analyzing the movie the researcher applied qualitative method and applies feminism approach especially liberal feminism theory by Naomi Wolf (1997). The data were collected by reading the movie script comprehensively and identify the utterances based on the problems. After that the data were analyzed by applying Wolf’s theory. The results show that the female characters experience gender discrimination in work and gender discrimination in education because their gender as woman. Meanwhile although the female characters experience gender discriminations, the female characters in Hidden Figures movie also shows their power to have equal rights such as rejecting the help of man and proving themselves to be capable of man’s work, making direct verbal objection and protest toward male character, explaining about the importance of woman in work place, and also taking legal solution to fight for the fairness in education. The efforts apply power feminism concepts as Wolf suggest. Key words: Gender discrimination, liberal feminism, power feminism